Zakat Fitrah untuk Investasi Ternak Sapi: Tinjauan Hukum Islam dan Maqashid Syariah : Zakat al-Fitr for Cattle Farming Investment: A Review of Islamic Law and Maqashid Sharia - Muslim; Alim, Muhammad Nurul (ITB AAS INDONESIA Surakarta, 2025)
This study critically examines the distribution of zakat al-fitr as business capital for cattle farming from the perspective of Islamic law and maqashid shariah. The main focus lies in the potential misalignment between the long-term productive use of zakat and the immediate, consumptive nature of zakat al-fitr, which must be distributed before the Eid prayer. Using a qualitative approach, this research applies textual analysis of Islamic legal sources and comparative fiqh to evaluate the practice. The findings reveal that while productive zakat may be valid for zakat mal, its application to zakat al-fitr contradicts the objective of thum’atan lil masakin (feeding the poor) and the principle of taʿjil (prompt distribution). Investment schemes like cattle farming require time to yield benefits, making them incompatible with the urgent spiritual and social function of zakat al-fitr. Therefore, the study concludes that such practice diverges from its maqashid and recommends zakat al-fitr be distributed in a consumable form to the needy on Eid day. This distinction is crucial for ensuring that zakat al-fitr fulfills its intended socio-spiritual role while empowering communities through other Islamic philanthropic instruments.